Organizational Memory Information System: Case Study in Faculty of Computer Science & Information System, UTM - Hamidi, Saidatul Rahah; Abdul Rahman, Azizah (2006)
The paper's purposes IS to evaluate the need for organizational memory information system (OMIS) in Faculty of Computer Science and Information System to improve academic management. Approach adopted in this research is to implement OMIS characteristics. After examining few models of organizational memory in literature review, OMIS characteristics is identified for implementation and success factor model to assess the OMIS. There are three possible forms of OMIS, namely paper documents, computer documents and self-memory. IT-based memory is quasi-permanent; knowledge is logged, indexed, secured and organized in such a way that it becomes accessible. IT contributes to organizational memory in at least two ways; by making accumulated knowledge accessible to organization members or by making individuals with knowledge known. OMIS could be achieved by effectively applying framework of OMIS, which include elements of individual, culture, transformation, structure, ecology, external environment, computer based information system and non-IT record and files. This paper indicates that there are 5 blocks of success factor to evaluate OMIS implementation; system quality, information quality, success measure in terms of usage, individual impact and organizational impact. The research is proposed as a prototype to be implemented for the whole module of FSKSM in order to protect their intellectual capital and optimizing the efficiency by managing organizational memory. The paper provides details of solution to academic management on the approach to making organizational memory information system work in practice. The approaches to manage memories in the model have yielded a number of benefits as demonstrated by a case study. This work will be beneficial to researchers and practitioner who are interested in applying OMIS in organization. Organization will be more efficient and gain competitive advantage with the utilization of collective memories. These memories can be in a form of data, information, or knowledge regarding problem solving and decision making. 1 Which is inefficient organization will re-do process and research to the same area for the same problem or situation. Besides, this lack of memories due to staff replacement can cause a "corporate amnesia" (Borghoff and Pareschi, 1998; Kransdorff, 1998). As a result, we need to construct an Organizational Memory (OM). OM is defined as a method for acquisition, retention, retrieval and knowledge accessible for organizational purposes (Walsh and Ungson, 1991). OM also called "corporate knowledge" or "corporate genetic" by Pralahad and Hamel (1994) and "corporate memory" by Annie (1999). Rose et al. (1998) also use the term "corporate memory" for knowledge repository that being used as a knowledge management tool. rganizational memory information system case study in Faculty of Computer Science & Information System, UTM (PDF Download Available). Available from: https://www.researchgate.net/publication/228889243_rganizational_memory_information_system_case_study_in_Faculty_of_Computer_Science_Information_System_UTM [accessed Aug 30, 2017].